2007
DOI: 10.2174/157015907780866884
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid CB2 Receptor as a Target for Inflammation-Dependent Neurodegeneration

Abstract: Endocannabinoids are released following brain injury and may protect against excitotoxic damage during the acute stage of injury. Brain injury also activates microglia in a secondary inflammatory phase of more widespread damage. Most drugs targeting the acute stage are not effective if administered more than 6 hours after injury. Therefore, drugs targeting microglia later in the neurodegenerative cascade are desirable. We have found that cannabinoid CB2 receptors are upregulated during the activation of microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
256
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(262 citation statements)
references
References 69 publications
6
256
0
Order By: Relevance
“…The CB1 receptor, uniquely recognized by cannabinoids, is found in brain and peripheral tissue of the central nervous system (CNS), 23 while the CB2 receptor is primarily found outside the CNS in tissues associated with immune function. 24 The availability of high-potency marijuana on the illicit market with unprecedented Δ 9 -THC concentrations (>20% by dry weight) 25 has renewed our interest in the discovery of new constituents from C. sativa L. We herein report the isolation and structure elucidation of 11 new esters from a high-potency variety of cannabis. These esters are β-fenchyl Δ 9 -tetrahydrocannabinolate (1), epi-bornyl Δ 9 -tetrahydrocannabinolate (2), α-terpenyl Δ 9 -tetrahydrocannabinolate (3), 4-terpenyl Δ 9 -tetrahydrocannabinolate (4), α-cadinyl Δ 9 -tetrahydrocannabinolate (5), γ-eudesmyl Δ 9 -tetrahydrocannabinolate (6), γ-eudesmyl cannabigerolate (7), 4-terpenyl cannabinolate (8), bornyl Δ 9 -tetrahydrocannabinolate (9), α-fenchyl Δ 9 -tetrahydrocannabinolate (10), and α-cadinyl cannabigerolate (11).…”
mentioning
confidence: 95%
“…The CB1 receptor, uniquely recognized by cannabinoids, is found in brain and peripheral tissue of the central nervous system (CNS), 23 while the CB2 receptor is primarily found outside the CNS in tissues associated with immune function. 24 The availability of high-potency marijuana on the illicit market with unprecedented Δ 9 -THC concentrations (>20% by dry weight) 25 has renewed our interest in the discovery of new constituents from C. sativa L. We herein report the isolation and structure elucidation of 11 new esters from a high-potency variety of cannabis. These esters are β-fenchyl Δ 9 -tetrahydrocannabinolate (1), epi-bornyl Δ 9 -tetrahydrocannabinolate (2), α-terpenyl Δ 9 -tetrahydrocannabinolate (3), 4-terpenyl Δ 9 -tetrahydrocannabinolate (4), α-cadinyl Δ 9 -tetrahydrocannabinolate (5), γ-eudesmyl Δ 9 -tetrahydrocannabinolate (6), γ-eudesmyl cannabigerolate (7), 4-terpenyl cannabinolate (8), bornyl Δ 9 -tetrahydrocannabinolate (9), α-fenchyl Δ 9 -tetrahydrocannabinolate (10), and α-cadinyl cannabigerolate (11).…”
mentioning
confidence: 95%
“…For instance in the brain of Alzheimer patients where activated microglia cluster at β-amyloid plaques. [2][3][4][5] CB2 increase is also reported for the rat chronic lesion model of Huntington's disease, especially in the striatum. [6] Furthermore, both hypoxia-ischemia and middle cerebral artery occlusion induced an up-regulation in the expression of CB2 in proliferating microglia in rat brain.…”
Section: Introductionmentioning
confidence: 53%
“…An increase in CB 2 expression has previously been exclusively described in models involving MCAO [4,13,15]. Ashton et al showed clusters of CB 2 and CD45 + microglia/ macrophages via immunohistochemistry and Western blot in the ischaemic penumbra at 3 days after MCAO until at least 7 days after surgery [15].…”
Section: Discussionmentioning
confidence: 93%
“…Most of the available drugs target the penumbra, which has been defined as brain tissue that is functionally impaired but potentially salvageable if treated in time [3]. Unfortunately, there is just a small time window of opportunity so that most of the drugs that work in the acute phase are ineffective if administered more than 6 h after cerebral ischaemia [4]. Hence, elaborate research and drug development for stroke are indispensable.…”
Section: Introductionmentioning
confidence: 99%